DIVERSIFIKASI REKSADANA DI INDONESIA BERDASARKAN METODE REWARD TO DIVERSIFICATION (RDIV) - , Nurasri Diah Sutiawati ([Yogyakarta] : Universitas Gadjah Mada, 2011)
This research is aimed to observe the development of mutual funds in Indonesia based on reward to diversification (RDIV) method, to rank the performance of mutual funds in Indonesia through the amount of risk that can be diversified by establish a portfolio or mutual fund, and to prove that mutual funds in Indonesia could diversify the risk optimally. This research employs archive strategy as the scheme for data collecting and data source is obtained from a secondary data, which is the net asset value (NAV) mutual funds in Indonesia which are dominated by equity and debt securities for the period of January 2005-December 2010. The writer successfully obtained 25 fixed-income funds, 17 balanced funds and 16 equity funds. The analytical method used is by counting the whole components of RDIV. This research represents that the development scale of risk which cannot be diversified by mutual funds in Indonesia are classified as good, except for fixedincome funds. The fluctuation of RDIV value moves in the same pattern, its decrease in the end of observation period. On average, the smallest risk which cannot be diversified is by equity funds, then by fixed-income funds and the largest risk is by balanced funds. However, if it assessment based on trade of between return and risk, equity funds is the first, balanced funds is the second, and fixed-income funds is the third. Furthermore, mutual funds in Indonesia have not been able to diversify risk optimally. Only equity funds are capable to diversify optimally more than fixed-income funds.